Molding Helmet Therapy for Deformational Brachycephaly. Issue 6 (September 2019) - Hallac, Rami R.; Ajiwe, Tochi; Effendi, Maleeh; Seaward, James R.; Kane, Alex A.
Abstract : Background: Molding helmet therapy is used for the treatment of infants with deformational brachycephaly (DB). There is a lack of rigorous outcome measures of helmet therapy in patients with DB using 3-dimensional (3D) imaging, with most reports rely on either subjective or 2-dimensional analyses. Furthermore, the longitudinal assessment of head shape improvement over the course of helmet therapy has not been documented. Our goal was to assess the outcome of molding helmet therapy using 3D surface imaging, and to document the pace of improvement during treatment. Methods: The head shape of 18 infants with DB who underwent orthotic molding helmet therapy was assessed. The 3D scans were obtained before treatment, during treatment, and at the end of treatment. First, we applied shape analysis techniques based on template deformation to obtain average (composite) heads of the 18 patients at the 3 time points of treatment (pretreatment, during, and posttreatment). In addition, we used 3D curvature analysis to quantify the degree of flatness at the same time points. Results: Molding helmet therapy started at 6.7 ± 0.9 months of age and lasted for 4.3 ± 0.8 months. The overall difference in the occipital contour between pretreatment and end of treatment was 6.3 ± 1.7 mm. Curvature analysis revealed that 15% of the back of the head had prehelmet marked flatness (mean curvature <5/m), which decreased to 9% at 2.5 months into treatment and 7% at the end of treatment. Conclusion: Over 65% of the head shape improvement occurred during the 2.5 months of molding helmet therapy.